Common causes and trends of hepatocellular carcinoma at regional cancer centre Raipur, India - Chandrakar, Pradeep K.; Choudhary, Vivek; Azad, Surendra K.; Beck, Manjula (International Journal of Research in Medical Sciences, 2018)
Background: Hepatocellular Carcinoma (HCC) is the most common primary malignancy of the liver and is the third most common cause of cancer related deaths in Asia-pacific region. Representative data on epidemiology of HCC in India is scanty and mostly from urban areas. It is more common in males then female. Hepatitis, alcohol consumption, aflatoxin and other hepatotoxins in diet are common causes. Authors did a study for the common causes and trends of the HCC registered at authors’ centre between January 2013 to November 2018. Methods: Authors analyzed their hospital data for the patient registered with the diagnosis of hepatocellular carcinoma at their centre during the study period for age, sex, number and causes. Results: Out of 23,766 patients registered for cancer in study period, 132 (0.55%) patients were of HCC, of which 89 (66.4%) were males and 43 (32.6%) were females, with ratio of 2:1. Commonest age group was between 50-59 years 46 (34.6%) followed by 40-49years 26 (19.5%). No patients were below 20 years of age. Among the commonest causes were alcohol consumption in 71 (53.4%), hepatitis B in 37 (27.8%), hepatitis C in 10 (7.5%), HIV in 4 (3%) and unknown in 11 (8.3%). There is rising trend in males and declining trend in females. Conclusions: Incidence of hepatocellular carcinoma is low among all cancer but has high mortality rate. Alcohol consumption and hepatitis were the commonest cause. It is common above 40 years specially in males.